Antioxidant and Free Radical Scavenging Activities of Selected Kenyan Leafy Vegetables - Chepkwony, C. I.; Cherutoi, K. J.; Munyendo, L. W.; Amdany, R. (Africa Environmental Review Journal, 2020)
Naturally occurring antioxidants found in vegetables and fruits can play a critical role in deactivating free radicals often before they attack biological cells in humans. Indigenous Kenyan vegetables are potential sources of antioxidants due to their richness in phytochemicals. The study investigated free radical scavenging activities of two indigenous vegetables; Solanum nigrum (black night shade) and Gynandropsis gynandra (spider plant), and two exotic vegetables; Brassica olearacea C. (cabbage) and Brassica olearacea A. (kale), during dry and wet seasons. Fresh leaf samples were collected randomly during the two seasons. Burnt Forest (BF), Elgeyo Border (EB), Kapseret (KSS), Kesses (KS) and Moiben (MB) in Uasin Gishu County, Kenya, were used as sampling areas. Sample processing was carried out in the laboratory prior to analysis using UV-Vis spectroscopy. Radical scavenging potential values for the vegetable samples were 89% (black night shade), 79% (spider plant), 55% (kale) and 35% (cabbage). All species exhibited a 2, 2- diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging activity with Solanum nigrum and Gynandropsis gynandra demonstrating greater antioxidant potential. It was also observed that extracts of black night shade and spider plant exhibited higher reducing capacities than their exotic counterparts (kale and cabbage) with values ranging from 38.9±3.3 to 937.3±16.5 µmol Fe2+ g-1 for cabbage and black night shade, respectively. The order of increasing reducing capacities of samples followed the trend: cabbage, kale, spider plant and black night shade. It was concluded that indigenous vegetables demonstrated better reducing potential capacities as shown by their higher DPPH radical scavenging values compared to the exotic vegetables and this is indicative of their superior antioxidative power. The agroclimatic conditions of a sampling site also influenced the antioxidant potential of a vegetable.